THE RELATIONSHIP BETWEEN ISLAMIC WORK ETHICS AND EMPLOYEE PERFORMANCE AMONG MEDICAL STAFF IN THE PUBLIC HEALTH SECTOR IN BAHRAIN: EMPLOYEE COMMITMENT AS MEDIATING VARIABLE - Ali Ahmed Ateeq Ali
This study discusses the relationship between Islamic work ethics and medical employee performance in the public sector under the Ministry of Health at the Kingdom of Bahrain using employee commitment as the intermediate variable. Weak employee commitment in the health sector leads to increasing number of complaints by patients and their families as evidenced by the increasing amount of medical errors during the last seven years. Descriptive quantitative method was employed using questionnaire to collect data. The study population reached 9,816 employees and out of 370 participants only (n=273) responded. Random stratified sampling according following Krejcie and Morgan (1970) model was employed, involving 370 doctors, nurses and pharmacists worked in the public sector under the Ministry of Health. The questionnaire's survey were (60) distributed in three axes. SPSS was used to analyse data, hypotheses, skewness and kurtosis test, exploratory factor analysis (EFA), Cronbach alpha coefficient and correlation matrix. Meanwhile, confirmatory factor analysis (CFA) and structural model equation (SEM) through the use of AMOS program were also used. The findings reveal that there is a direct positive relationship between Islamic work ethics and employee performance and there is a direct positive link between Islamic work ethics and employee commitment. Furthermore, there is an indirect impact relationship between Islamic work ethics and employee performance through employee commitment as an intermediate variable. This confirms that employee commitment reinforces and improves the relationship between Islamic work ethics and employee performance. In terms of the implications of this study, it will receive great attention from human resources management (HRM) specialists and senior management as they look for ways to increase quality medical services and reduce complaints and medical errors by increasing awareness on the Islamic work ethics